Report of the Ministerial Committee on the Nigerian Brain Drain. - Nigeria: Federal Ministry of Information (Lagos : Federal Ministry of Information, Printing Division, 1974)
This reports contains a details findings of the 1974 ministerial committee to examine the rate of brain drain in Nigeria.
Cover title.
At head of title: Federal Republic of Nigeria.
Includes bibliographical references.
asm 23/01/2019
Loans
Keywords: Brain drain; Labour mobility; Nigeria